Development and validation of fingerprints ofTurnera diffusaextracts obtained by use of high-performance liquid chromatography with diode array detection and chemometric methods - Garza Juárez, A.; Waksman de Torres, Noemí; Ramírez Durón, Rosalba; Salazar Cavazos, M. L. (2009)
A high-performance liquid chromatographic method with diode-array detection (HPLC–DAD) has been developed and validated to establish the fingerprint of Turnera diffusa. Hydroalcoholic extracts were obtained from 19 raw herbal samples collected in different regions of México. Separation was performed on a 150 mm × 3.9 mm (4-μm particle) C18 column, using a gradient of methanol and 0.1% aqueous trifluoroacetic acid as the mobile phase. Chromatograms were recorded at 254 nm. To identify each peak, both retention time and peak spectrum were used. Intraday and interday relative standard deviations were <3% for retention time and <12% for relative areas. Extracts were stable in solution for up to 60 days. Results from a robustness study showed that the amount of ethanol in the mobile phase had a substantial effect on retention time. The relative areas of 12 peaks common to the chromatograms obtained from 19 authenticated T. diffusa samples were chosen to construct a principal-components analysis (PCA) model. The soft independent modeling of class analogy (SIMCA) method based on the PCA model was used to evaluate the quality of eleven commercial products.